Training on the Use of Digital Learning Media (DGMATH and DGDL) for Elementary and Middle School Teacher in Pacitan Regency - Yuniarti, Dwi Ariani Finda; Hikmahwan, Bagus; Fu’adi, Anwar; Putra, Berlian Juliartha Martin; Nugroho, Berto Yusuf (International Journal of Public Devotion, 2025)
Education plays a vital role in a nation's progress, particularly in the digital era, which demands the integration of technology into teaching and learning processes. Digital-native generations, such as Generation Z and Alpha, who are familiar with technology, require a learning approach based on digital tools. However, in Pacitan Regency, the implementation of digital learning media faces challenges such as inadequate facilities, limited training and low digital literacy among teachers. This study aims to enhance teachers' competencies through training in the use of digital learning applications, namely DGMATH (Digital Mathematics) and DGDL (Digital Differentiation Learning). DGMATH is an Android-based application designed for elementary school students, offering mathematics content in an interactive educational game format.DGDL, a web-based application, supports differentiated learning,  enabling teachers to adapt materials   to students' individual needs. Both applications have been tested and proven to increase students' motivation and learning outcomes.  The training was conducted at AKN Pacitan, involving 30 elementary and junior high school teachers. Evaluation results showed that all four trainin indicators—content, facilitator quality, facilities, and benefits—received scores above 80%, indicating the effectiveness of the training. Participants reported increased confidence in utilizing technology to create interactive and meaningful learning experiences. This training contributes to improving the quality of education by empowering teachers with digital literacy skills. Recommendations include sustaining the training program, developing application features, and expanding participant outreach to support the transformation of technology-based education in remote areas like PacitanPelatihan Penggunaan Media Pembelajaran Digital (DGMATH dan DGDL) bagi Guru SD dan SMP di Kabupaten PacitanABSTRAKPendidikan berperan vital dalam kemajuan bangsa, terutama di era digital yang menuntut integrasi teknologi dalam proses belajar mengajar. Generasi digital  native  seperti  Generasi  Z  dan  Alpha  yang akrab dengan teknologi memerlukan pendekatan pembelajaran berbasis digital. Namun, di Kabupaten Pacitan, implementasi media pembelajaran digital masih terkendala kurangnya fasilitas, minimnya pelatihan, dan rendahnya literasi digital guru. Penelitian ini bertujuan meningkatkan kompetensi guru melalui pelatihan penggunaan aplikasi pembelajaran digital, yaitu DGMATH (Digital Matematika) dan DGDL (Digital Differentiation Learning). DGMATH adalah aplikasi berbasis Android yang dirancang untuk siswa SD, menghadirkan materi matematika dalam format game edukatif yang interaktif. DGDL, berbasis web, mendukung pembelajaran berdiferensiasi, memudahkan guru menyesuaikan materi sesuai kebutuhan siswa. Kedua aplikasi ini telah diuji dan terbukti meningkatkan motivasi serta hasil belajar siswa. Pelatihan dilaksanakan di AKN Pacitan dengan partisipasi 30 guru SD dan SMP. Hasil evaluasi menunjukkan keempat indikator pelatihan, yakni materi, kualitas fasilitator, fasilitas, dan manfaat, memperoleh nilai >80%, menunjukkan efektivitas pelatihan. Peserta  merasa  lebih  percaya diri  dalam memanfaatkan  teknologi  untuk menciptakan pembelajaran interaktif dan bermakna. Pelatihan ini berkontribusi pada peningkatan kualitas pendidikan  melalui  pemberdayaan  guru  dalam literasi digital. Keberlanjutan pelatihan, pengembangan fitur aplikasi, serta perluasan jangkauan peserta menjadi rekomendasi untuk mendukung transformasi pendidikan berbasis teknologi di daerah terpencil seperti Pacitan.Kata Kunci :DGMATH; Pembelajaran Diferensiasi; Media Pembelajaran Digital